The effect of audit quality on downward real earnings management: U.K. evidence - Lyu, Yu (2018)
I examine whether the enhancement of audit quality leads to the increasing use of downward real earnings management among firms with incentives to deflate earnings. For a sample of the UK listed firms that have at least one announcement of share repurchases, MBOs and option awards during 2009-2017, I find that higher audit fee is associated with more downward real earnings management. The effect of audit quality in three corporate events and earnings smoothing is tested separately. I find that firms seem to engage in more downward real earnings management prior to share repurchases and option awards, while MBOs and earnings smoothing have a counter effect of the audit quality on downward real earnings management.